Building experiments in PsychoPy - Peirce, Jonathan (Sage, 2018)
PsychoPy is an open-source (free) software package for creating rich, dynamic experiments in psychology, neuroscience and linguistics. It provides an intuitive graphical interface (the "Builder") as well as the option to insert Python code. This combination makes it easy enough for teaching, but also flexible enough for all manner of behavioural experiments. As a result, PsychoPy has become the software package of choice in psychology departments at universities all over the world. Divided into three parts and with unique learning features to guide readers at whatever level they are at, this textbook is suitable for teaching practical undergraduate classes on research methods, or as a reference text for the professional scientist. The book is written by Jonathan Peirce, the original creator of PsychoPy and Michael MacAskill who have utilised their breadth of experience in Python development to educate students and researchers in this intuitive, yet powerful, experiment generation package.